Obras raras na Biblioteca Pública do Amazonas: critérios de raridade - Santos, Anamilce Gomes dos (Brasil, 2024)
This work deals with rarity criteria in the Amazonas Public Library. The general objective of this work is to analyze the rarity criteria adopted by the library through the collection formation and development policy document for the Library Department of the Amazonas State Secretariat for Culture and Creative Economy (DB/SEC). Among specific objectives: Describe the historical framework of BPAM; identify the rarity criteria used in the BPAM collection; describe PLANOR's criteria for rare works in comparison to BPAM's policy. It addresses the role of the public library, presents the concept of rare works from the point of view of the authors who deal with the topic, discusses the National Library and its formation and the origin of PLANOR, describes the creation of the Amazonas Public Library and the fire which occurred in 1945, destroying its entire collection, leaving 60 works that were in an exhibition. Examine the criteria adopted by the public library and check how close they are to PLANOR. In order to analyze the criteria used by the library, the draft of the collection formation and development policy document made available by BPAM was examined. Based on the information received, it was found that the library does not have a policy for rare collections, just one document still in the approval phase, this document is used internally as a guide to assist in the qualification of rare works, where it was possible to identify in this document the criteria adopted by the library with PLANOR and those designed to meet the specificities of Amazonian works.